2009
DOI: 10.1519/jsc.0b013e3181bac2ab
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Strength of Police Officers With Gender Comparisons

Abstract: Strength is a critical factor in the health and job performance of police officers. Using a retrospective longitudinal design, the purpose of this study was to identify differences in strength scores from initial recruitment to in-service tests and to compare gender differences. Strength changes were also compared in low- to high-strength groups. Strength scores included bench press, bench press/lean weight, and bench press/weight. Body weight, percent body fat, and bench press scores were retrieved for the 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 19 publications
7
61
2
Order By: Relevance
“…The authors reported that female officers had approximately 44% of the upper body strength of male officers and attributed this positive finding to maintaining ongoing fitness training and testing by departments. Differences in sample size, types of testing and study design may account for some of the differences in findings between our study and those of the Boyce et al [33].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The authors reported that female officers had approximately 44% of the upper body strength of male officers and attributed this positive finding to maintaining ongoing fitness training and testing by departments. Differences in sample size, types of testing and study design may account for some of the differences in findings between our study and those of the Boyce et al [33].…”
Section: Discussioncontrasting
confidence: 64%
“…Contrary results have been found in other studies. For example, Boyce et al [33] found in a 12.5-year longitudinal study of police fitness that both male and female officers increased in strength well into their 30s and 40s. The authors reported that female officers had approximately 44% of the upper body strength of male officers and attributed this positive finding to maintaining ongoing fitness training and testing by departments.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 2 and 3 show that training for police officers was less goal-oriented and that fewer police officers used training programmes. According to Boyce, Jones, Schendt, Lloyd, and Boone (2009), these results are problematic. Boyce et al (2009) emphasised the importance of implementing a structured physical fitness programme in a police environment with the objective of promoting improvement over time.…”
Section: Reductions In Physical Activity and Use Of Training Goals Anmentioning
confidence: 99%
“…Considering that critical situations, which demand high intensity physical involvement, do occur independent of the officer's age and physical fitness these findings are disturbing. A lowered physical fitness level related to increased age could seemingly have a negative impact on the result of the situation [3,10]. Regarding stature, body mass and BMI correlated with the physical index and the arrest index, no significant findings were disclosed.…”
Section: Discussionmentioning
confidence: 88%
“…However, due to regularly emerging episodes of high physical exertion the occupation can still be physically demanding. Such episodes are often occurring acute and can be stressful, critical and even life threatening for both the officer and the surrounding civilians [1,3]. So even if the major part of the job can be executed independent of a police officers' physical fitness, some tasks still demand certain level of physical fitness to be handled and if the officer is not capable of managing these tasks as well, it can be questioned if he or she is capable of doing the job at all.…”
Section: Introductionmentioning
confidence: 99%